Optical studies of tellurium based quaternary glasses - Sreenivasulu, V.; Prasad, M. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The glasses with composition 64TeO2-15CdO-(20-x)ZnO-xBaO-1V2O5 (x= 0, 5, 10, 15 and 20 mol%) were prepared by conventional melt quenching technique. X-ray diffraction method was used to confirms the non crystalline behavior of the glass samples. The optical absorption studies shows that the cut-off wavelength decreases while optical band gap energy (Eopt) and Urbach energy (∆E) values increase with an increase of BaO composition. The Refractive index ( ) calculated from Eopt was found to decrease with an increase of BaO mol percentage. The physical parameters such as density (ρ), molar volume (Vm), oxygen packing density (OPD), molar refraction (Rm) and metallization criterion (M) estimated and discussed.